Effect of strains and parts on amino acids of Dendrobium officinale - Liu, Zhen-peng; Guo, Ying-ying; Iu, Jing-jing; Si, Jin-ping; Wu, Ling-shang; Zhang, Xin-feng (Zhongguo zhongyao zazhi, 2015)
The aim of the paper is to reveals the variations of Dendrobium officinale amino acids in different strains and parts for breeding excellent varieties, and providing scientific basis for the expanding of medicinal or edible parts. The contents of 17 amino acids in 11 strains of D. officinale were determined by hydrochloric acid hydrolysis method. The total amino acids content of leaves was from 6.76 to 7.97 g per 100 g, and the stems was from 1.61 to 2.44 g per 100 g. As the content of amino acids in leaves was significantly higher than that of stems, and the composition was close to the ideal protein standard proposed by FAO/WHO. The leaves of D. officinale had the good prospect for the development of functional foods. The 9 x 66 strain which with high yield and polysaccharide content had the highest amino acids content both in stems and leaves, indicated crossbreeding could improve the quality of varieties. Compared the amino acids content of D. officinale in two main harvest periods, the harvest time has a significant impact on amino acids content of D. officinale. This study demonstrates that the harvesting time of D. officinale stems is suitable for leaves as well, which is the period before bolssom.